2016
DOI: 10.1093/ageing/afv201
|View full text |Cite
|
Sign up to set email alerts
|

Older care-home residents as collaborators or advisors in research: a systematic review

Abstract: Background: patient and public involvement (PPI) in research can enhance its relevance. Older care-home residents are often not involved in research processes even when studies are care-home focused.Objective: to conduct a systematic review to find out to what extent and how older care-home residents have been involved in research as collaborators or advisors.Methods: a systematic literature search of 12 databases, covering the period from 1990 to September 2014 was conducted. A lateral search was also carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 25 publications
3
90
0
2
Order By: Relevance
“…Our findings reinforce the call for patient‐centred care, that is, health care that is responsive to the preferences, needs and values of each patient regardless of whether the goals of care are curative and interventional or focused on a palliative approach. Our findings also support the need to include consumer voices in facilitating health service improvement …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our findings reinforce the call for patient‐centred care, that is, health care that is responsive to the preferences, needs and values of each patient regardless of whether the goals of care are curative and interventional or focused on a palliative approach. Our findings also support the need to include consumer voices in facilitating health service improvement …”
Section: Discussionsupporting
confidence: 75%
“…This qualitative study involved public consultation and representation of views including those of different ages, ethnicity and experience of health care. Involving older people as advisors has shown to enhance the relevance of health services research . The information collected in our consultation covered recent experiences in the health system and home settings and is of relevance for clinicians and health service planners.…”
Section: Discussionmentioning
confidence: 99%
“…Older people are often not involved in research processes even when studies are care‐home‐focused (Backhouse et al, ). Some studies that have focused on the decision‐making processes surrounding the move have highlighted that older adults rarely initiate relocation decisions relying instead on family, professionals or both to determine when relocation is called for (Fraher & Coffey, ; Keister, ; Reed, Cook, Sullivan, & Burridge, ).…”
Section: Introductionmentioning
confidence: 99%
“…Engaging patient partners in clinical research has been shown to be feasible and to have a variety of positive outcomes . However, in geriatric oncology research, specific mechanisms and the logistics of assembling a patient and caregiver partner stakeholder group that is mutually beneficial to both the research team and the stakeholder group to the best of our knowledge has not yet been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging patient partners in clinical research has been shown to be feasible and to have a variety of positive outcomes. 10 However, in geriatric oncology research, specific mechanisms and the logistics of assembling a patient and caregiver partner stakeholder group that is mutually beneficial to both the research team and the stakeholder group to the best of our knowledge has not yet been thoroughly explored. Herein, we described our patient partner engagement in study optimization, shape, conduct, and the dissemination of research findings using PCORI's 6 principles as a guide: 1) reciprocal relationships; 2) co-learning; 3) partnerships; 4) transparency; 5) honesty; and 6) trust.…”
Section: Introductionmentioning
confidence: 99%